Research Into improved Distance Learning Using VR Technology - Li, Pengfei; Fang, Zelong; Jiang, Tan (Frontiers in Education, 2022)
Practical skills’-based education requires face-to-face exemplary operation teaching. Based on VR means, online distance learning can be achieved, "face-to-face" teaching of teacher-student communication can be achieved, learners' self-efficacy and on-site experience can be improved, and learners' learning effectiveness can be improved.This study will use a mixed study of quantitative and qualitative combination, using document collation, case analysis and comparative analysis, and VR teaching using "You,Calligrapher" as a survey tool.Randomly select teachers and students who are related to art, and use VR calligraphy educational game applications for teaching activities.Investigate the impact of VR time and space and technical availability on learners' understanding, imagination and interactivity on VR education, and then have a positive impact on learners' feedback on learning effects evaluation.Research tools include comprehension, imagination, feedback motivation scales for learning effects, and Chinese calligraphy skills’ performance tests.Use SPSS statistical analysis software for related statistical processing, and set to 0.05.The results of this study found that Chinese calligraphy studies in VR time and space will affect students' understanding and imagination, but not their operational interactivity.According to the experimental results, it is shown that the change of VR education to the practice teaching method is the most essential feature different from traditional teaching and the Internet teaching. Therefore, the focus of this study is to understand the impact mechanism of the practical skills’ distance learning to achieve the effect, forming a VR education strategy thinking.